Nepal : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Since the transition to democracy, the government of Nepal has pursued policies intended to promote a modern market-oriented economy. Inflation continues to be strongly influenced by supply shocks and price developments in India. There have been improvements in the external position with continued reserve accumulation, and the real effective exchange rate has remained stable. Budget performance reflects the prevailing weaknesses in overall fiscal policy implementation. Some progress has been made in the areas of price reform, privatization, and financial sector reform.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet